What determines performance satisfaction in mountain ultra marathon runners? An exploration of coping, resilience, and mental toughness - Beattie, S.; Poretlli, N.; Woodman, T. (International Journal of Sport and Exercise Psychology, 2025)
Subjective perceptions of performance form an integral part of an athlete's ability to self-regulate behaviour during competitive events. In cases where an athlete perceives performance is not going as well as expected, they may apply additional coping strategies to get back on track. If coping strategies employed are perceived as being effective, post-race performance satisfaction will consequently increase. However, research findings hint that the relationship between coping effectiveness and performance satisfaction may be influenced by other higher-order psychological factors, such as mental toughness (MT) and resilience. The purpose of this study was to test new hypotheses regarding possible interactive effects that MT and resilience have upon coping effectiveness in predicting performance satisfaction. A sample of 47 mountain ultra-marathon runners completed one assessment of MT and two assessments of resilience before competing in the Madeira Island Ultra Trail (MIUT 115). Post-race, participants completed measures of coping effectiveness, coping frequency, and performance satisfaction. The results revealed that coping effectiveness had a positive and significant relationship with performance satisfaction under increasing levels of MT and resilience; no significant relationship emerged when MT and resilience were low. From a within-race perspective, coping frequency had a linear trend across time for those who were satisfied with their race performance, whereas a quadratic relationship was revealed for those who were less satisfied with their performance. A second purpose of the study was to briefly examine coping strategy effectiveness and performance satisfaction from a qualitative perspective. Applied implications are discussed.